"Tworzenie kraju" (Making Country) jako zasada przekładalności treści mitycznych na rytualne w tradycjach aborygeńskich - Szyjewski, Andrzej (Uniwersytet Wrocławski. Pracownia Badań nad Tradycją Oralną, 2017)
The analysis of Australian mythical and ceremonial scenarios proves that for Aboriginal myth, ritual, song and landscape relate to each other, eventually creating a context of intermingling metaphorical constructs, based on the “creation of country” principle. During oral transmission the songs and features of the landscape are subject to small changes; however, they are not immutable (the landscape remains the same, but the interpretation of specific characteristics are subject to change). The syntagmatic order of the myth is arranged mainly around spatial displacements. In accordance with Róheim’s thesis it is very difficult to understand the complex network of meanings when analyzing only one of its elements; therefore, research should combine analysis of myth, ritual, song and landscape. An appropriate procedure should incorporate synchronous analysis as well as exegesis of material from Aboriginal informants, which allow us to set certain events within their cultural framework and, above all, give the myth a narrative character.
Keywords: Aborygeni Australijscy; mit; rytuał; pieśni obrzędowe; Pitjantjatjara; metaforyzacja; tworzenie kraju